Genetic defects in a His-Purkinje system transcription factor, IRX3, cause lethal cardiac arrhythmias - Koizumi, Akiko; Sasano, Tetsuo; Kimura, Wataru; Miyamoto, Yoshihiro; Aiba, Takeshi; Ishikawa, Taisuke; Nogami, Akihiko; Fukamizu, Seiji; Sakurada, Harumizu; Takahashi, Yoshihide; Nakamura, Hiroaki; Ishikura, Tomoyuki; et al. (European heart journal, 2016)
Ventricular fibrillation (VF), the main cause of sudden cardiac death (SCD), occurs most frequently in the acute phase of myocardial infarction: a certain fraction of VF, however, develops in an apparently healthy heart, referred as idiopathic VF. The contribution of perturbation in the fast conduction system in the ventricle, the His-Purkinje system, for idiopathic VF has been implicated, but the underlying mechanism remains unknown. Irx3/IRX3 encodes a transcription factor specifically expressed in the His-Purkinje system in the heart. Genetic deletion of Irx3 provides a mouse model of ventricular fast conduction disturbance without anatomical or contraction abnormalities. The aim of this study was to examine the link between perturbed His-Purkinje system and idiopathic VF in Irx3-null mice, and to search for IRX3 genetic defects in idiopathic VF patients in human. Telemetry electrocardiogram recording showed that Irx3-deleted mice developed frequent ventricular tachyarrhythmias mostly at night. Ventricular tachyarrhythmias were enhanced by exercise and sympathetic nerve activation. In human, the sequence analysis of IRX3 exons in 130 probands of idiopathic VF without SCN5A mutations revealed two novel IRX3 mutations, 1262G>C (R421P) and 1453C>A (P485T). Ventricular fibrillation associated with physical activities in both probands with IRX3 mutations. In HL-1 cells and neonatal mouse ventricular myocytes, IRX3 transfection up-regulated SCN5A and connexin-40 mRNA, which was attenuated by IRX3 mutations. IRX3 genetic defects and resultant functional perturbation in the His-Purkinje system are novel genetic risk factors of idiopathic VF, and would improve risk stratification and preventive therapy for SCD in otherwise healthy hearts.